Hubungan Anemia pada Ibu Hamil dengan Antropometri dan Apgar Score Bayi Baru Lahir di Rumah Sakit Dr. Tadjuddin Chalid Kota Makassar - Rahayu, Sri; Nurdin, Azizah; Rahim, Rosdianah (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Introduction: Anemia is one of the problems in pregnant women that can affect anthropometry of newborns that contain weight, body length and head circumference as well as the newborn score. The aim of this study was to determine the relationship between anemia of pregnant women to anthropometry and the apgar score of newborns at Dr. Tadjuddin Chalid Hospital Makassar. Methods: The method used in this research is observational analytic with cross sectional design. Sampling was done by purposive sampling. The total sample of 269 deliveries at Dr. Tadjuddin Chalid Hospital Makassar. The research data were sourced from secondary data such as patient identity, anemia of pregnant women, infant anthropometry which included weight, length, head circumference, and apgar score measured immediately after birth. Results: The results of this study indicate that anemia of pregnant women are significantly related to newborn body weight (p = 0.007), newborn body length (p = 0.011), newborn head circumference (p = 0.039), and anemia of pregnant women does not have a significant relationship with the apgar of newborns score (p = 0.088). Conclusion: The conclusion of this study is that anemia status of pregnant women has a relationship with anthropometry of newborns on the parameters of body weight, body length, head circumference of newborns and anemia status of pregnant women has no relationship with the apgar score of newborns.